A supplementary description of Cypridina mariae and rediagnosis of the genus Cylindroleberis (Ostracoda - Syme, A. E.; Poore, G. C. B. (Myodocopa: Cylindroleberididae). PLoS One, 2008)
The ostracod family Cylindroleberididae is based on the genus Cylindroleberis Brady, 1868, and has a complicated nomenclatural history. The type species of Cylindroleberis is Cypridina mariae Baird, 1850. Baird described only the carapace, which had been considered lost. Thus, there was no reference point for the concept C. mariae or the genus Cylindroleberis. Baird's material has now been found in the Natural History Museum, London, U.K., and is illustrated here. To clarify the taxonomic status of C. mariae and Cylindroleberis, specimens were obtained from near the type locality, and a supplementary description is presented. This includes description of appendages, particularly the first antenna and mandible, which contain important diagnostic characters. This supplementary description provides important information about C. mariae, allowing a revision of the genus Cylindroleberis, and establishing a framework for future biological research on this ostracod group.